THE FINITE-STATE PLAYGROUND - Hammond, Michael (International Journal of English Studies, 2008)
Finite-state methods are finding ever increasing use among linguists as a way of modeling phonology and morphology and as a method for manipulating and modeling text. This paper describes a suite of very simple finite-state tools written by the author that can be used to investigate this area and that can be used for simple analysis.